Flexible composite material based on cork and preparation method and application thereof
Delignifying wood with sodium chlorite and impregnating it with organosilane enhances wood's flexibility and thermal insulation, addressing flammability and water absorption issues, suitable for construction, aviation, and automobiles.
Patent Information
- Application Number
- CN202411662046.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-01-03
AI Technical Summary
Wood's flammability and water absorption limit its application in construction and industrial fields due to the durability issues of traditional coatings, which fail to provide long-term fire and water resistance.
A method involving delignification of wood with sodium chlorite solution, followed by impregnation with an organosilane and surfactant mixture, forming an organosilicon-lignin hybrid material that enhances thermal insulation and flame retardancy by creating a silica ceramic layer during combustion.
The process improves the flexibility, fire resistance, and thermal insulation of wood-based materials, enabling their use in construction, aviation, and automobiles, while maximizing resource utilization and reducing environmental impact.
Smart Images

Figure CN119238673A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a flexible composite material based on cork and a preparation method and application thereof, belonging to the technical field of fireproof composite materials and preparation thereof. Background Art
[0002] As a natural sustainable material, wood is widely present in the natural environment and is easy to obtain. Its main components are cellulose, hemicellulose and lignin. According to the internal structure, it can be divided into softwood and hardwood. The internal structure of softwood is honeycomb, and the structure of hardwood is fibrous. Common softwoods include pine, balsa, fir, and poplar, and common hardwoods include oak, birch, maple, and sandalwood. However, the traditional characteristics of wood make it have certain defects in the fields of fire prevention and heat insulation, mainly manifested in flammability and water absorption, which limits its application in the construction and industrial fields.
[0003] Lignin is a complex organic polymer that provides wood with hardness and resistance to decay. It is a biopolymer widely found in wood tissues. It hardens the cell wall by forming an interwoven network, plays a compressive role, and has the functions of avoiding biological invasion, water erosion, antibacterial, antioxidant, anti-ultraviolet absorption and flame retardant. Lignin is the only renewable aromatic compound resource in nature, which makes it a sustainable source of thermal insulation materials.
[0004] Although lignin itself has certain thermal insulation properties, its effect is not significant, mainly because lignin contains a large number of phenolic hydroxyl and methoxy groups, which are prone to oxidation reactions at high temperatures. At the same time, lignin has a high porosity, and the heterogeneity and connectivity of its porous structure will increase the path for heat to be conducted through the solid matrix.
[0005] In order to solve the flammability of wood, the existing solutions are mainly to coat the wood surface with flame retardants or waterproof coatings, but these methods can usually only provide limited fire and water resistance. Due to the durability of the coating itself, these protective layers are prone to peeling and failure after long-term use or in harsh environments, resulting in a significant decrease in their protective performance. In actual applications, there are problems such as poor durability and high cost. Summary of the invention
[0006] In view of the above-mentioned deficiencies in the prior art, the present invention provides a method for preparing a flexible composite material based on cork, the method comprising the following steps:
[0007] (1) delignifying wood with a sodium chlorite solution to obtain wet delignified wood and a sodium chlorite solution containing lignin;
[0008] (2) repeatedly filtering and rinsing the wet delignified wood with anhydrous ethanol until the pH is 7.0±0.5 to obtain delignified wood;
[0009] (3) adding alkali to the sodium chlorite solution containing lignin to neutralize it to a pH of 7, and then adding a catalyst, an auxiliary agent, a surfactant and an organosilane, mixing them evenly to obtain an impregnation solution;
[0010] (4) The delignified wood obtained in (2) is subjected to multiple suction filtration and impregnation treatments using the impregnation solution prepared in (3), followed by heating and drying to obtain a softwood-based flexible composite material.
[0011] It is further defined that the wood in (1) is pine, balsa, fir or poplar with a thickness not exceeding 100 mm.
[0012] It is further defined that the mass fraction of the sodium chlorite solution in (1) is 1-5%, the solvent is a polar solvent, and glacial acetic acid is used to adjust the pH of the sodium chlorite solution to 3.5-5.
[0013] In a further embodiment, the polar solvent is deionized water, anhydrous ethanol, ethylene glycol or methanol.
[0014] It is further defined that the mass volume ratio of the wood to the sodium chlorite solution in (1) is 0.002 to 0.0096 g / mL.
[0015] It is further defined that the delignification process in (1) is: adding the wood to a sodium chlorite solution, heating to boiling and maintaining boiling for 2-5 hours.
[0016] It is further defined that the filtration and rinsing process in (2) is as follows: the wet delignified wood is placed in a Buchner funnel, soaked in anhydrous ethanol for 5-10 minutes, and then filtered using a vacuum pump. This process is repeated 3-6 times until the pH is 7.0±0.5.
[0017] Further specified, (3) the alkali is sodium hydroxide, ammonia water, sodium carbonate or sodium bicarbonate; the catalyst is one or a mixture of glacial acetic acid, oxalic acid, hydrochloric acid and sulfuric acid; the auxiliary agent is ammonia water and / or urea; the surfactant is one or a mixture of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, sodium dodecyl sulfonate, sodium dodecyl sulfate, triethanolamine stearate and dodecylpyridinium chloride; the organosilane is a mixture of two of dimethyldimethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, dimethyldiethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, aminopropyltrimethoxysilane and 3-aminopropyltriethoxysilane.
[0018] It is further defined that the mass ratio of the catalyst, the auxiliary agent, the surfactant, the organosilane and the sodium chlorite solution containing lignin in (3) is (0.5-1):(30-50):(5-10):(10-20):100.
[0019] It is further defined that the process of filtration and impregnation in (4) is as follows: the delignified wood is placed in a Buchner funnel, impregnated with the impregnation solution for 5-10 minutes, and then filtered with a vacuum pump, and the process is repeated 3 to 6 times.
[0020] It is further defined that the heating and drying treatment temperature in (4) is 40-60°C and the time is 4-7h.
[0021] The second object of the present invention is to provide a cork-based flexible composite material prepared by the above method.
[0022] The third object of the present invention is to provide an application of the above-mentioned cork-based flexible composite material, specifically a fireproof material for the fields of construction, aviation and automobile.
[0023] Beneficial effects:
[0024] The present invention first uses a boiling chemical solution to remove lignin from cork, so that pores are formed between the cellulose fibers of the cork to provide space for the deformation of the cellulose. The removed lignin is then blended with silane to form a precursor solution, which is mixed with the delignified wood. After filtration, impregnation, heating and gel drying, an organosilicon-lignin hybrid material is formed. The organosilicon aerogel is used to fill the pores between the cellulose fibers and is coated on the surface of the cellulose to form a coating, thereby reducing the pore size of the original natural structure and improving the thermal insulation performance. In addition, during the combustion process, the organosilicon-lignin hybrid material can be pyrolyzed in situ to form a silica ceramic layer, which effectively blocks oxygen penetration and exhibits flame retardant properties that the original natural wood does not have. The impregnation of flexible aerogel gives the material macroscopic flexibility, so that the obtained composite material has flexibility. Compared with the prior art, the present invention has at least the following advantages:
[0025] (1) The present invention uses organosilicon aerogel to modify wood, which not only retains the natural microchannel structure of wood, but also improves the anti-aging property of wood and prolongs the service life of wood-based composite materials. In addition, organosilicon aerogel has excellent heat insulation and flame retardant properties, which enables wood to overcome the limitations in high temperature environments. Previously, the material components such as hemicellulose and lignin removed during the preparation process were reused and eventually became the components of the composite material, realizing the full utilization of natural wood, ensuring the maximization of resource utilization, reducing the negative impact on the environment, and solving technical problems in the sustainable utilization of wood resources and environmental friendliness.
[0026] (2) The present invention utilizes the organosilanols after the hydrolysis of organosilicon to react chemically with the lignin in the remaining solution and the lignin that has not been removed from the original wood, wherein the aliphatic hydroxyl or carboxyl group of the lignin reacts with the silanols to form lignin-organosilicon. The organosilanols increase the linear chain length of the lignin, thereby increasing the deformation freedom of the molecules and increasing the flexibility of the composite material.
[0027] (3) The present invention first uses a boiling chemical solution to delignify the cork, so that more hydroxyl groups are exposed on the wood surface, which is convenient for the subsequent chemical reaction with another part of the free organosilicon (which has not reacted with lignin), so that the organosilicon is cross-linked on the surface of the delignified wood, and the remaining organosilicon silanol undergoes a self-condensation reaction and adheres to the surface of the delignified wood. In the final heating and drying process, the molecules that are not attached to the delignified wood form a layer of organosilicon film on the wood surface under the action of capillary force, thereby further improving the fireproof and heat-insulating properties of the wood.
[0028] (4) The present invention uses green renewable resource wood as raw material, and utilizes the high porosity, good microchannel structure, and natural honeycomb structure of the material itself. After compounding with flexible aerogel, the composite material has flexibility and improves the mechanical, fire retardant, heat insulation, and thermal insulation properties of wood. It can be widely used in construction, aviation, automobiles, and other fields.
[0029] (5) The present invention effectively shortens the production cycle and improves production efficiency by delignifying the original wood, impregnating it with an organosilicon aerogel precursor solution, and directly heating it after impregnation to perform gelation and drying. The preparation process is simple and low in cost, and the process is suitable for large-scale industrial production, which has good market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a SEM photograph of the balsa wood treated in Comparative Example 1 along the growth direction;
[0031] Figure 2 This is a SEM photograph of the delignified wood obtained in Example 1 along the growth direction;
[0032] Figure 3 This is a SEM photo of the composite material obtained in Example 1 along the growth direction;
[0033] Figure 4 This is a SEM photograph of the composite material obtained in Comparative Example 3 along the growth direction;
[0034] Figure 5 This is a SEM photograph of the composite material obtained in Comparative Example 2 along the growth direction;
[0035] Figure 6 Schematic diagram of the flexibility of the composite material obtained in Example 1;
[0036] Figure 7 This is a photo of the combustion performance test of the composite material obtained in Example 1;
[0037] Figure 8 This is a photo of the combustion performance test of balsa wood treated by Comparative Example 1;
[0038] Fig. 9 FTIR spectra comparison diagram of the composite material, delignified wood and balsa wood obtained in Example 1;
[0039] Fig.10 This is a photograph of the composite material obtained in Example 1 after combustion. DETAILED DESCRIPTION
[0040] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0041] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0042] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0043] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained by those skilled in the art through commercial channels, and the purity of the solid and liquid reagents used is analytically pure.
[0044] In the following examples, the density of balsa wood is 0.1 g / cm 3 , tensile strength is 11MPa, limiting oxygen index is 22%, and thermal conductivity is 55mW / (m·K).
[0045] Example 1
[0046] The specific process of preparing the organosilicon aerogel-impregnated delignified wood composite material in this embodiment is as follows:
[0047] S1. Cut balsa wood into 20mm×20mm×2mm size;
[0048] S2, preparing a sodium chlorite solution with a mass fraction of 2% with water as a solvent, and adjusting the pH to 4.6 with acetic acid to obtain a delignified solution;
[0049] S3, immersing the balsa wood in a beaker of the prepared delignified solution and heating, adjusting the heating temperature to 175° C. to maintain a boiling state, heating for 2 hours to obtain wet delignified wood and a delignified solution containing lignin;
[0050] The mass volume ratio of balsa wood to sodium chlorite solution is 0.0064 g / mL;
[0051] S4, placing the wet delignified wood obtained in S2 into a Buchner funnel, soaking it in anhydrous ethanol for 5 minutes and then filtering it with a vacuum pump, repeating the above soaking and filtering process 5 times to remove the residual acetic acid and sodium chlorite solution until the pH is 7, and obtaining delignified balsa wood for standby use;
[0052] The microstructure of the delignified balsa wood was characterized. Figure 2 As shown by Figure 2 It can be seen that a scale-like structure appears along the growth direction and adheres to the pore surface, the pore wall becomes thinner, and some lignin and cellulose are removed.
[0053] S5, adding alkali to neutralize the delignified solution containing lignin obtained in S3 to a pH of 7, then adding acetic acid, a surfactant, urea, and siloxane, and placing the solution in a magnetic stirrer for thorough stirring to obtain an impregnation solution;
[0054] The mass ratio of acetic acid, surfactant, urea, siloxane and sodium chlorite solution containing lignin is 0.03:6.06:33.34:33:100; siloxane is prepared by mixing methyltrimethoxysilane (MTMS) and diethoxydimethylsilane (DMDES) in a mass ratio of 3:2; the surfactant is hexadecyltrimethylammonium bromide;
[0055] S6. Place the delignified balsa wood treated by S4 into a Buchner funnel, immerse it in the impregnation solution prepared in S5 for 5 minutes, and then filter it with a vacuum pump. Repeat this process 5 times; place it in a 40°C oven for direct gel drying for 4 hours to obtain a silicone aerogel-impregnated delignified wood composite material.
[0056] The microstructure of the composite material was characterized. Figure 3 As shown by Figure 3 It can be seen that a uniform silica aerogel film is formed on the pore surface of delignified balsa wood, while retaining the original channel structure.
[0057] Fig. 9The FTIR spectra of the composite material, delignified wood and balsa wood obtained in Example 1 are compared. As can be seen from the figure, 2922 cm -1 The peak at 2360 cm-1 comes from the methyl group on the benzene ring. -1 The absorption peak of hydroxyl group is at 1742cm. The weakening of this peak in the composite material indicates that the hydrophilicity is reduced. -1 C=O, 1050cm -1 The CO absorption peak at 2968 cm-1 is weakened in the composite and delignified wood, indicating that some lignin has been removed. -1 、1034cm -1 、800cm -1 The peaks are Si-OC, Si-O-Si and Si-C, which come from the hydrolysis and condensation between MTMS and DMDES.
[0058] The flexibility of the composite material was tested, and the results were as follows: Figure 6 As shown by Figure 6 It can be seen that under the action of external force, the composite material will bend and deform, and will not suffer brittle failure. Compared with the brittle original wood, the mechanical properties are greatly improved.
[0059] Example 2
[0060] The specific process of preparing the organosilicon aerogel-impregnated delignified wood composite material in this embodiment is as follows:
[0061] S1. Cut balsa wood into 20mm×20mm×2mm size;
[0062] S2, preparing a sodium chlorite solution with a mass fraction of 2% with water as a solvent, and adjusting the pH to 4.6 with acetic acid to obtain a delignified solution;
[0063] S3, immersing the balsa wood in a beaker of the prepared delignified solution and heating, adjusting the heating temperature to 175° C. to maintain a boiling state, heating for 3 hours to obtain wet delignified wood and a delignified solution containing lignin;
[0064] The mass volume ratio of balsa wood to sodium chlorite solution is 0.0064 g / mL;
[0065] S4, placing the wet delignified wood obtained in S2 into a Buchner funnel, soaking it in anhydrous ethanol for 5 minutes and then filtering it with a vacuum pump, repeating the above soaking and filtering process 5 times to remove the residual acetic acid and sodium chlorite solution until the pH is 7, and set aside;
[0066] S5, adding alkali to neutralize the delignified solution containing lignin obtained in S3 to a pH of 7, then adding acetic acid, a surfactant, urea and siloxane, and placing the solution in a magnetic stirrer for sufficient stirring to obtain an impregnation solution;
[0067] The mass ratio of acetic acid, surfactant, urea, siloxane and sodium chlorite solution containing lignin is 0.03:6.06:33.34:33:100; siloxane is prepared by mixing methyltrimethoxysilane (MTMS) and diethoxydimethylsilane (DMDES) in a mass ratio of 3:2; the surfactant is hexadecyltrimethylammonium bromide;
[0068] S6. Place the delignified balsa wood treated by S4 into a Buchner funnel, impregnate it with the impregnation solution prepared in S5 for 5 minutes, and then filter it with a vacuum pump. Repeat this process 5 times; place it in a 40°C oven for direct gel drying for 4 hours to obtain a silicone aerogel impregnated delignified composite material.
[0069] Example 3
[0070] The specific process of preparing the organosilicon aerogel-impregnated delignified wood composite material in this embodiment is as follows:
[0071] S1. Cut balsa wood into 20mm×20mm×2mm size;
[0072] S2, preparing a sodium chlorite solution with a mass fraction of 2% with water as a solvent, and adjusting the pH to 4.6 with acetic acid to obtain a delignified solution;
[0073] S3, immersing the balsa wood in a beaker of the prepared delignified solution and heating, adjusting the heating temperature to 175° C. to maintain a boiling state, heating for 4 hours to obtain wet delignified wood and a delignified solution containing lignin;
[0074] The mass volume ratio of balsa wood to sodium chlorite solution is 0.0064 g / mL;
[0075] S4, placing the wet delignified wood obtained in S2 into a Buchner funnel, soaking it in anhydrous ethanol for 5 minutes and then filtering it with a vacuum pump, repeating the above soaking and filtering process 5 times to remove the residual acetic acid and sodium chlorite solution until the pH is 7, and set aside;
[0076] S5, adding alkali to neutralize the delignified solution containing lignin obtained in S3 to a pH of 7, then adding acetic acid, a surfactant, urea, and siloxane, and placing the solution in a magnetic stirrer for thorough stirring to obtain an impregnation solution;
[0077] The mass ratio of acetic acid, surfactant, urea, siloxane and sodium chlorite solution containing lignin is 0.03:6.06:33.34:33:100; siloxane is prepared by mixing methyltrimethoxysilane (MTMS) and diethoxydimethylsilane (DMDES) in a mass ratio of 3:2; the surfactant is hexadecyltrimethylammonium bromide;
[0078] S6. Place the delignified balsa wood treated by S4 into a Buchner funnel, impregnate it with the impregnation solution prepared in S5 for 5 minutes, and then filter it with a vacuum pump. Repeat this process 5 times; place it in a 40°C oven for direct gel drying for 4 hours to obtain a silicone aerogel impregnated delignified composite material.
[0079] Example 4
[0080] The specific process of preparing the organosilicon aerogel-impregnated delignified wood composite material in this embodiment is as follows:
[0081] S1. Cut balsa wood into 20mm×20mm×2mm size;
[0082] S2, preparing a sodium chlorite solution with a mass fraction of 2% with water as a solvent, and adjusting the pH to 4.6 with acetic acid to obtain a delignified solution;
[0083] S3, immersing the balsa wood in a beaker of the prepared delignified solution and heating, adjusting the heating temperature to 175° C. to maintain a boiling state, heating for 5 hours to obtain wet delignified wood and a delignified solution containing lignin;
[0084] The mass volume ratio of balsa wood to sodium chlorite solution is 0.0064 g / mL;
[0085] S4, placing the wet delignified wood obtained in S2 into a Buchner funnel, soaking it in anhydrous ethanol for 5 minutes and then filtering it with a vacuum pump, repeating the above soaking and filtering process 5 times to remove the residual acetic acid and sodium chlorite solution until the pH is 7, and set aside;
[0086] S5, adding alkali to neutralize the delignified solution containing lignin obtained in S3 to a pH of 7, then adding acetic acid, a surfactant, urea, and siloxane, and placing the solution in a magnetic stirrer for thorough stirring to obtain an impregnation solution;
[0087] The mass ratio of acetic acid, surfactant, urea, siloxane and sodium chlorite solution containing lignin is 0.03:6.06:33.34:33:100; siloxane is prepared by mixing methyltrimethoxysilane (MTMS) and diethoxydimethylsilane (DMDES) in a mass ratio of 3:2; the surfactant is hexadecyltrimethylammonium bromide;
[0088] S6. Place the delignified balsa wood treated by S4 into a Buchner funnel, impregnate it with the impregnation solution prepared in S5 for 5 minutes, and then filter it with a vacuum pump. Repeat this process 5 times; place it in a 40°C oven for direct gel drying for 4 hours to obtain a silicone aerogel impregnated delignified composite material.
[0089] Comparative Example 1
[0090] S1. Cut the balsa wood into 20mm×20mm×2mm size;
[0091] S2. Place the cut balsa wood in a beaker and place it in an ultrasonic cleaner for 30 minutes;
[0092] S3, put the balsa wood obtained by shaking in S2 into a Buchner funnel, soak it in anhydrous ethanol for 5 minutes and then filter it with a vacuum pump. Repeat this process 5 times to wash away the impurities on the surface and inside of the wood;
[0093] S4. Place the washed balsa wood in S3 into a 40°C oven for drying.
[0094] The microscopic morphology of the treated balsa wood was characterized. Figure 1 As shown by Figure 1 It can be seen that balsa wood has a tubular structure with honeycomb-shaped cavities along the growth direction, clear cell wall boundaries, loose connections between cells, and high porosity, which makes balsa wood softer. Due to fewer fiber cells and thin cell walls, its compressive and bending strengths are low, and cells are easily deformed and broken when subjected to external forces.
[0095] Comparative Example 2
[0096] The specific process of preparing the organosilicon aerogel impregnated wood composite material in this embodiment is as follows:
[0097] S1. Cut the balsa wood into 20mm×20mm×2mm size;
[0098] S2. Place the cut balsa wood in a beaker and place it in an ultrasonic cleaner for 30 minutes;
[0099] S3, put the balsa wood obtained by shaking in S2 into a Buchner funnel, soak it in anhydrous ethanol for 5 minutes, and then filter it with a vacuum pump. Repeat this process 5 times to wash away the impurities on the surface and inside of the wood, and obtain wet balsa wood for use;
[0100] S4, preparing an impregnation solution. Deionized water, acetic acid, surfactant, urea, and siloxane are added in sequence, and the mixture is placed in a magnetic stirrer for thorough stirring to obtain a precursor solution;
[0101] The mass ratio of acetic acid, surfactant, urea, siloxane and deionized water is 0.03:6.06:33.34:33:100; siloxane is prepared by mixing methyltrimethoxysilane (MTMS) and diethoxydimethylsilane (DMDES) in a mass ratio of 3:2; the surfactant is hexadecyltrimethylammonium bromide;
[0102] S5. Put the wet balsa wood obtained in S3 into a Buchner funnel, impregnate it with the impregnation solution prepared in S4 for 5 minutes, and then filter it with a vacuum pump. Repeat this process 5 times; put it into a 40°C oven for direct gel drying for 4 hours to obtain a silicone aerogel-impregnated wood composite material.
[0103] The microstructure of the composite material was characterized. Figure 5 As shown by Figure 5 It can be seen that the surface membrane has uneven texture and fractures, and the wood structure has disappeared.
[0104] Comparative Example 3
[0105] The specific process of preparing the organosilicon aerogel-impregnated delignified wood composite material in this embodiment is as follows:
[0106] S1. Cut balsa wood into 20mm×20mm×2mm size;
[0107] S2, preparing a sodium chlorite solution with a mass fraction of 2% with water as a solvent, and adjusting the pH to 4.6 with acetic acid to obtain a delignified solution;
[0108] S3, immersing the balsa wood in a beaker of the prepared delignified solution and heating it, adjusting the heating temperature to 175° C. to maintain a boiling state, heating for 2 hours to obtain wet delignified wood;
[0109] The mass volume ratio of balsa wood to sodium chlorite solution is 0.0064 g / mL;
[0110] S4, placing the wet delignified wood obtained in S2 into a Buchner funnel, soaking it in anhydrous ethanol for 5 minutes and then filtering it with a vacuum pump, repeating the above soaking and filtering process 5 times to remove the residual acetic acid and sodium chlorite solution until the pH is 7, and set aside;
[0111] S5, adding deionized water, acetic acid, hexadecyltrimethylammonium bromide, urea, and siloxane in sequence, placing in a magnetic stirrer for thorough stirring to obtain an impregnation solution;
[0112] The mass ratio of acetic acid, surfactant, urea, siloxane and deionized water is 0.03:6.06:33.34:33:100; siloxane is prepared by mixing methyltrimethoxysilane (MTMS) and diethoxydimethylsilane (DMDES) in a mass ratio of 3:2; the surfactant is hexadecyltrimethylammonium bromide;
[0113] S6. Place the delignified balsa wood treated by S4 into a Buchner funnel, immerse it in the impregnation solution prepared in S5 for 5 minutes, and then filter it with a vacuum pump. Repeat this process 5 times; place it in a 40°C oven for direct gel drying for 4 hours to obtain a silicone aerogel-impregnated delignified wood composite material.
[0114] The microstructure of the composite material was characterized. Figure 4 As shown by Figure 4 It can be seen that the surface film is uneven, with flocculent structures accumulated on the surface and obvious fracture marks. Figure 3 contrast, Figure 3 The surface film grows evenly and smoothly without obvious fracture cracks.
[0115] Effect example
[0116] (1) The mechanical properties and heat resistance of the composite materials prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were tested, and the results are shown in Table 1 below;
[0117] Table 1
[0118]
[0119] As can be seen from the above table, the thermal conductivity of Examples 1 to 4 is lower than that of the original wood, and the limiting oxygen index is higher than that of Comparative Examples 1 to 3. This is because the organosilicon aerogel impregnated with wood has excellent thermal insulation performance. The uniform and dense nanopore and microchannel structure can effectively prevent air convection, reduce thermal radiation and heat conduction, which makes the wood impregnated with organosilicon aerogel also have thermal insulation performance. At the same time, the reuse of lignin in the preparation makes the organosilicon-lignin hybrid material formed after the heating gel is dried to form a film on the cellulose surface, which reduces the pore size of the original natural structure and improves the thermal insulation performance. Although the tensile strength is lower than that of the original wood, the low density and good thermal insulation and flame retardant properties are conducive to the use of the material as a lightweight structural material that requires a certain mass but cannot be too heavy.
[0120] (2) A combustion test was performed on the composite material prepared in Example 1 and the balsa wood treated in Comparative Example 1. Figure 7 and Figure 8 The following are photos of burning for 15 seconds. Figure 7 and Figure 8It can be seen that the composite material prepared in Example 1 exhibits better flame retardancy than balsa wood. Fig.10 This is a photo of the composite material obtained in Example 1 after combustion. Fig.10 It can be seen that the composite material prepared in Example 1 has good flame retardant properties.
[0121] Although the present invention has been disclosed as above in the preferred embodiments, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing a flexible composite material based on cork, characterized in that: include: (1) delignifying wood with a sodium chlorite solution to obtain wet delignified wood and a sodium chlorite solution containing lignin; (2) repeatedly filtering and rinsing the wet delignified wood with anhydrous ethanol until the pH is 7.0±0.5 to obtain delignified wood; (3) adding alkali to the sodium chlorite solution containing lignin to neutralize it to a pH of 7, and then adding a catalyst, an auxiliary agent, a surfactant and an organosilane, mixing them evenly to obtain an impregnation solution; (4) The delignified wood obtained in (2) is subjected to multiple suction filtration and impregnation treatments using the impregnation solution prepared in (3), and then subjected to heating and drying treatments to obtain a softwood-based flexible composite material.
2. The preparation method according to claim 1, characterized in that: (1) Medium wood is pine, balsa, fir or poplar with a thickness not exceeding 100 mm.
3. The preparation method according to claim 1, characterized in that: (1) The mass fraction of the sodium chlorite solution is 1-5%, the solvent is a polar solvent, and glacial acetic acid is used to adjust the pH of the sodium chlorite solution to 3.5-5.
4. The preparation method according to claim 1, characterized in that: (1) The mass volume ratio of the wood to the sodium chlorite solution is 0.002 to 0.0096 g / mL.
5. The preparation method according to claim 1, characterized in that: (1) The delignification process is as follows: the wood is added to a sodium chlorite solution, heated to boiling and kept boiling for 2-5 hours.
6. The preparation method according to claim 1, characterized in that: (3) The alkali is sodium hydroxide, ammonia water, sodium carbonate or sodium bicarbonate; the catalyst is one or a mixture of glacial acetic acid, oxalic acid, hydrochloric acid and sulfuric acid; the auxiliary agent is ammonia water and / or urea; the surfactant is one or a mixture of hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, sodium dodecyl sulfonate, sodium dodecyl sulfate, triethanolamine stearate and dodecylpyridinium chloride; the organosilane is a mixture of two of dimethyldimethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, dimethyldiethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, aminopropyltrimethoxysilane and 3-aminopropyltriethoxysilane.
7. The preparation method according to claim 1, characterized in that: The mass ratio of the catalyst, the auxiliary agent, the surfactant, the organosilane and the sodium chlorite solution containing lignin in (3) is (0.5-1):(30-50):(5-10):(10-20):
100.
8. The preparation method according to claim 1, characterized in that: (4) The immersion time of the filtration immersion is 5-10 minutes, and the number of repetitions is 3-6 times; the heating and drying treatment temperature is 40-60°C, and the time is 4-7 hours.
9. A cork-based flexible composite material prepared by the method according to any one of claims 1 to 8.
10. An application of the cork-based flexible composite material according to claim 9, characterized in that: Fireproof materials used in construction, aviation and automotive fields.